Comparative Evaluation of Activated Carbon and Granulated Blast Furnace Slag in Treating Greywater - Iqbal, Fatima (2020)
A Master of Science thesis in Civil Engineering by Fatima Iqbal entitled, “Comparative Evaluation of Activated Carbon and Granulated Blast Furnace Slag in Treating Greywater”, submitted in May 2020. Thesis advisors are Dr. Kazi P. Fattah and Dr. Md. Maruf Mortula. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form). Embargo expires February 25, 2021.